Front Office as a Green Hotel Practice at Novotel Bali Ngurah Rai Airport - Mega Angeli Pakpahan; I Ketut Sutama; I Ketut Suparta; Raden Roro Rieta Anggraheni (International Journal of Glocal Tourism, 2022)
Purpose: This study aimed to determine the readiness of the Front Office Department towards a green hotel through the implementation of green practice at the Novotel Bali Ngurah Rai Airport. Research methods: This research data collection method was carried out by observation, interviews, literature study and documentation. The data analysis technique uses descriptive qualitative analysis to determine whether the implication of green practice at Novotel Bali Ngurah Rai Airport has gone to a green hotel or not. Findings:The results show that 90% of green practice has been implemented in the Front Office Department of Novotel Bali Ngurah Rai Airport where of the 3 green practice indicators with a total of 10 sub-indicators, 9 of them have been implemented and 1 has not been implemented in the Front Office Department at Novotel Bali Ngurah Rai Airport is on the green action indicator with sub-indicators doing recycling. Implication: The Front Office Department at Novotel Bali Ngurah Rai Airport is almost eligible to support Novotel Bali Ngurah Rai Airport to become a green hotel.